The Bangkok Declaration and Strategy for Aquaculture Development Beyond 2000 and Philippine Aquaculture - Danilo C. Israel; Rolando R. Platon (Philippine Institute for Development Studies (PIDS), 2001)
This paper reviews the Philippine aquaculture sector in light of the Bangkok Declaration and Strategy for Aquaculture Development Beyond 2000, an internationally produced document that strongly encourages the incorporation of key strategy elements into the national aquaculture development programs. The purpose of the paper is to identify constraints to the full incorporation of the key strategy elements into the local aquaculture program and recommend measures for addressing them. The paper found that the various key strategies mentioned in the Bangkok Declaration have already been implemented in the aquaculture sector to a significant extent. While so, however, much remains to be done to hasten the implementation of the strategies. In general, they will be better pursued if the Philippine Fisheries Code and the Agriculture and Fisheries Modernization Act are fully implemented. Adequate funding for the two laws must be provided to allow the establishment and operations of the different aquaculture institutions, programs, projects and activities they envisioned. Review of the contentious provisions of the two laws must also be conducted and amendments made at the appropriate time, if necessary. Streamlining of the different government institutions and functions involved in fisheries and aquaculture should be pursued to effect coordinated operations. Furthermore, increased support for training and extension is needed. In particular, the strengthening of regional offices of the Bureau of Fisheries and Aquatic Resources and the offices of the Local Government Units involved in extension must be given priority.
Keywords: 330; aquaculture sector; aquaculture development; key strategy elements for aquaculture development; Southeast Asian Fisheries Development Center; Aquakultur; Philippinen; Aquakultur